Напрями інноваційної модернізації промисловості України - Горощенко, В.В. (Стратегія і механізми регулювання промислового розвитку, 2013)
Наведено визначення понять «нерухомість», «управління нерухомістю»; розглянуто види послуг, які включає система управління нерухомістю у Європі; досліджено підсистеми об'єктів управління з наданням їх ключових характеристик; сформовано напрями цільового впливу теорії управління нерухомістю; подано трактування загальних і специфічних функцій ринку нерухомості; визначено значення землі як базового об'єкта нерухомості. Выявлено, что модернизация чаще всего рассматривается в трех аспектах, а именно: социальном, политическом и экономическом. Определены основные черты, которые присущи процессу модернизации, с учетом чего предложено определять модернизацию как многоуровневый комплексный процесс, который предусматривает поэтапную мобилизацию всех имеющихся ресурсов и их оптимизацию с целью проведения институциональных преобразований в финансово-экономической, социально-культурной, политической и других сферах общества. Раскрыты факторы, которые влияют на модернизацию промышленных предприятий. Предложены направления проведения инновационной модернизации промышленности Украины и обоснованы мероприятия по активизации процессов инновационной модернизации отечественной экономики и стимулирования ее структурной перестройки. The paper reveals that the modernization is often viewd in three aspects, namely the social, political and economic. Determined are the general features that are inherent in the process of modernization, namely: comprehensiveness, consistency, differentiated character, mobilization, territorial and temporal orientation which define the modernization as multi-layered and complex process that includes step-by mobilizing all available resources and their optimization with the aim of implementing the institutional reforms in the financial-economic, socio-cultural, political and other spheres of society. Disclosed are the objective, subjective, local, global, external and internal factors that influence the modernization of industrial enterprises. The ways of innovative modernization of industry of Ukraine, which require the optimization of the industry are offered which require the optimization of the industry, technological, organizational, regional and managerial structures of industry, and the measures are well-grounded to activate the innovative processes of modernization of the national economy and encourage structural adjustment among which are the accelerated depreciation of fixed assets, exemption from tax of a part of enterprise’s profit for the modernization, introduction of a delay ofpayment of import duties and taxes on introduction in Ukraine of equipment, which is directed to the modernization of the technical and technological base of the industrial enterprises, creating new jobs, focused on the goals of modernization and others.